Fuzzy‐based fake information detection algorithm to define the user trust on the content of social networks. Issue 6 (1st November 2019) - Nirmala, Munirathinam; Babu, Madda Rajasekhara
Abstract : Across the globe, right from people who are technologically naive to people who are with high‐technical knowledge, use, share, spread, and connect with each other through online social networks. People start believing and sharing the social network content without any proof of its authenticity. In several cases, the reliability of the information that gets shared between the users remains questionable due to the anonymity of the information creators. In this work, a fuzzy detection algorithm is proposed to identify the trustable content in social media. The proposed methodology is evaluated on Twitter social network platform. By computing the predictive measures, the efficiency of the proposed approach is well established.